Radiology department activity intravenous contrast media (IVCM) webinar/course 8.7.2023 - Mohd Razalli, Mazuin; Mohamad Ali, Norliana Dalila (Faculty of Medicine, 2023)
Hospital Al-Sultan Abdullah (HASA) Radiology Department has held the Intravenous Contrast Course (IVCC) annually since 2020. The course was initially held online due to the pandemic. However, we continue to do it online on weekends to encourage more participation from our department.